PELAKSANAAN PENILAIAN PERKEMBANGAN BAHASA ANAK RA IHYAUL QUR’AN KRANDON GUNTUR DEMAK - Rizkia Navi Maulida; Istiqomah Istiqomah; Indah Indriani; Fu'ad Arif Noor (JURNAL LENTERA ANAK, 2022)
The implementation of the assessment is the basis in the implementation of the learning assessment. Assessment in RA serves to collect various data and information regarding the growth and development of students in each activity. In conducting the assessment there are appropriate techniques and instruments in measuring child development by the teacher. The purpose of this study was to determine the implementation of the assessment of early childhood language development at RA Ihyaul Qur'an Krandon Guntur Demak. Methods This research uses a qualitative descriptive approach. Sources of primary data obtained by digging information directly through respondents using interview techniques and direct observation in the field. The primary data sources of this research are the results of interviews with classroom teachers and students. The secondary data source in this study used to support the primary data is the child's assessment document. Data collection techniques in this study are observation, interviews, and documentation studies. The results showed that the techniques and instruments for assessing early childhood language development at RA Ihyaul Qur'an Krandon Guntur Demak were as follows: (1) the teacher adjusted the instrument for assessing language development, observation, conversation, anecdotes, performance and work: (2 ) the teacher makes the form of language development assessment techniques and instruments (3) the limits of language development assessment (4) the teacher draws conclusions on the language development assessment for each assessment